Death of a Salesman: Miscarriage of American Dream and the Blight of Loman Family - Ghimire, Rishiram (Bon Voyage, 2024)
This article focuses on the play Death of a Salesman written by Arthur Miller in which the concept of American dream aborts in Willy’s life. The abortion of American dream results in American nightmare enervating hope and progress for everyone. Upward mobility of an individual as well as family in job, house, marriage, children, social status becomes the hope of everyone as American dream promises. However, the play Death of a Salesman reveals nightmare life of Loman family who are struggling for their better, richer and fuller life. Willy Loman’s pathetic end ridicules American dream that is thought to be panacea for all. This article, in terms of Willy Loman, analyzes how the concept of American dream ‘all men are created equal and everyone has skills and aptitudes to pull themselves up by their own efforts’ has been superficial and the country fosters American nightmare.